EVALUATING ELEARNING USER INTERFACE DESIGN IN MALAYSIAN PRIVATE HIGHER LEARNING INSTITUTIONS: A COMPARATIVE STUDY ON ACADEMIC LECTURERS’ EXPERIENCE - Mat Yusoff, Nur Huda; Azahari, Mustaffa Halabi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
eLearning platforms are widely adopted in Malaysia to enhance teaching and learning, yet its potential remains underexploited due to limitations in usability and interface design. This study investigates the user interface design (UID) of eLearning systems in private higher learning institutions (HLIs), emphasizing academic lecturers’ experiences and perceptions. A two-phase mixed-methods approach was applied and guided by the ADDIE instructional design model and the Unified Theory of Acceptance and Use of Technology (UTAUT). In the first phase, systematic observations were conducted to evaluate the UID of four private HLIs by focusing on visual presentation, layout, navigation, and interactivity. In the second phase, survey questionnaires were distributed to 200 academic lecturers to assess platform usability across five key dimensions: course quality, technical system quality, interactivity, visual design and UID quality. The findings reveal persistent usability challenges, including inconsistent layouts, text-heavy interfaces, poor navigation, and limited interactive elements. Survey results further demonstrate that these design shortcomings reduce lecturers’ satisfaction and discourage deeper engagement with eLearning functionalities. The study highlights UID as a critical determinant of system usability and effectiveness in private HLIs. By identifying specific design-related barriers, the research offers insights into user experience issues that hinder adoption and sustained use of digital learning platforms. These outcomes also support national educational goals aligned with Sustainable Development Goal 4 (SDG 4), which emphasizes inclusive and high-quality education through improved digital infrastructure in higher education. Also, the study provides a comprehensive framework for evaluating eLearning interface usability that can guide Malaysian HLIs in improving digital learning quality and adoption.